Bubble coalescence principle in saline water - Danlong Li; Rogerio Manica; Zhixiang Chen; Shuo Wang; Qingxia Liu; Haijun Zhang (Proceedings of the National Academy of Sciences, 2025)
Bubbles present in saline water typically exhibit a prolonged lifetime, making them attractive for various engineering processes. Herein, we unveil a transition from delayed bubble coalescence to rapid bursting within about one millisecond in salty solutions. The key aspect in understanding this transition lies in the combined influences of surface deformation and ion surface excess instead of characterizing the ions alone. Only with a sufficiently deformed region trapped between the colliding bubble and fluid surfaces can the coalescence inhibition effect be maintained to cause the bouncing behavior. Thus, we quantify a consistent upper limit of ion transfer content required for instant coalescence under different salty conditions. Furthermore, we present numerical ranges associated with different bubble behaviors in terms of E o , R e , and W e and determine the critical values to predict bubble dynamics. Our findings shed light on the bubble coalescence principle in saline water and allow access to the regulation of coalescence time based on the requirement of technological applications.